2006
DOI: 10.1109/glocom.2006.669
|View full text |Cite
|
Sign up to set email alerts
|

WLC10-2: Analytic Optimization of Hybrid ARQ Performance in Wireless Packet Data Systems

Abstract: Abstract-We propose an analytical framework that optimizes the performance of various Hybrid Automatic Repeat reQuest (HARQ) schemes in wireless packet data systems. The optimization framework lends itself to maximizing the user throughput without assuming a specific HARQ scheme, a target packet error rate, and a mapping of signal-to-interference-noise ratios (SINR) into modulation and coding scheme (MCS) sets. Thus, a user selects an optimal amount of redundancy bits used for retransmissions, an optimal packe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…In fact, although these schemes have been studied mostly as techniques to increase the throughput, as for instance in [6], [7], the recent literature reports an increasing interest on their energy efficiency. Collaborative and noncollaborative HARQ systems under an outage constraint are studied in [8], where it is shown that the optimal irradiated energy depends both on the number of retransmissions and on the consumption of the electronic components of the transceivers.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although these schemes have been studied mostly as techniques to increase the throughput, as for instance in [6], [7], the recent literature reports an increasing interest on their energy efficiency. Collaborative and noncollaborative HARQ systems under an outage constraint are studied in [8], where it is shown that the optimal irradiated energy depends both on the number of retransmissions and on the consumption of the electronic components of the transceivers.…”
Section: Introductionmentioning
confidence: 99%
“…Based on that, a tractable model was proposed in [31], and extensive simulation results in [32] also support the model. Cho et al [33] slightly modified the model and concluded that the ratio of the SNR increment per retransmission to the original SNR, i.e., ∆η/η 0 , is proportional to α: ∆η = gαη 0 , where the IR coding gain g ≥ 1 is weakly dependent on the modulation and coding scheme [31], [34], [32]. We adopt this basic model.…”
Section: A Drizzlementioning
confidence: 99%
“…With respect to parameter settings in our simulations, the ARQ retransmission timeout period is set to be 0.05 milliseconds. In HARQ IR, we set the maximum number of retransmissions to be 4, and the corresponding optimal size of redundancy packets based on the results in [33]. We set the packet size as 512 bits and the block size as 8 bits.…”
Section: A Drizzlementioning
confidence: 99%
“…The packet error rates in the additive white gaussian noise (AWGN) model are obtained through extensive simulations based on the technical specification document [1]. For HARQ, we only focus on Incremental Redundancy which is shown to achieve better performance than Chase Combining [14]. We set the maximum number of retransmissions to be 4, and the corresponding optimal size of redundancy packets based on the results in [14].…”
Section: Performance Evaluationmentioning
confidence: 99%
“…For HARQ, we only focus on Incremental Redundancy which is shown to achieve better performance than Chase Combining [14]. We set the maximum number of retransmissions to be 4, and the corresponding optimal size of redundancy packets based on the results in [14].…”
Section: Performance Evaluationmentioning
confidence: 99%